2021
DOI: 10.3390/healthcare9111483
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Dermal Suction on Passive Muscle and Joint Stiffness

Abstract: The aim of the present study was to examine the acute effects of dermal suction on the passive mechanical properties of specific muscles and joints. Dermal suction was applied to the calves of 24 subjects. Passive plantar flexion torque was measured with the right knee fully extended and the right ankle positioned at 20°, 10°, 0°, and −10° angles, where 0° represents the ankle neutral position, and positive values correspond to the plantar flexion angle. The shear wave velocity (SWV) (m/s) of the medial gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
(54 reference statements)
0
11
2
Order By: Relevance
“… 9 , 22 We also hypothesized that the changes in each of the methods will be in trivial or small correlations. 23 The findings of this study could be important for clinical practice and future research on muscle characteristics. Namely, we will reveal if (and to what extent) the shear modulus and passive joint torque measurement can be used interchangeably to infer changes in muscle stiffness.…”
Section: Ethical Publication Statementsmentioning
confidence: 78%
See 1 more Smart Citation
“… 9 , 22 We also hypothesized that the changes in each of the methods will be in trivial or small correlations. 23 The findings of this study could be important for clinical practice and future research on muscle characteristics. Namely, we will reveal if (and to what extent) the shear modulus and passive joint torque measurement can be used interchangeably to infer changes in muscle stiffness.…”
Section: Ethical Publication Statementsmentioning
confidence: 78%
“…While we are not aware of any studies that assessed changes in shear modulus alongside changes in passive joint torque after eccentric exercise, a recent study used both methods to assess changes induced by dermal suction therapy. 23 The authors reported statistically significant increases in shear modulus, and no changes in passive joint stiffness, 23 again pointing to a need for caution when using different methods to assess muscle stiffness.…”
Section: Ethical Publication Statementsmentioning
confidence: 99%
“…The painrelieving effect of cupping therapy in humans is explained by the aforementioned mechanism. However, there is no single theory that can explain the entire scope of its effect, and elucidation of its mechanism of action remains a challenge (Enomoto et al 2021). The pain-alleviating effect in horses may occur through the same mechanism as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A monitor on the main device shows the amount of negative pressure generated in real time (Figure 3). This device has been used in human research on dermal suctioning (Enomoto et al, 2021).…”
Section: Dermal Suctioningmentioning
confidence: 99%
“…Therefore, in previous research targeting only joint flexibility, what caused the change in joint ROM due to dermal suction was not clear. Focusing on this point, Enomoto et al (2021) attempted to elucidate part of the mechanism of joint flexibility improvement by dermal suction [ 10 ]. Enomoto et al (2021) measured the stiffness of the medial gastrocnemius (MG) immediately before and after dermal suction of the calf using shear wave elastography and discovered that passive muscle stiffness significantly increased immediately after dermal suction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%